Estudo e desenvolvimento de material absorvedor de micro-ondas baseado em Nb2O5 com mo via metalurgia do pó - Gurgel, Diêgo Pires (2016)
In Brazil are located the two largest niobium reserves of the world – about 96% of the world production – and, for this reason, have been encouraged studies on its most diverse technological applications. Another aspect of prominent studies is currently the processing of ceramic materials with a microwave, which is presented as an alternative method of sintering in a muffle furnace – the use of microwave involves electromagnetic energy conversion instead of heat transfer, offering advantages when used for providing the obtainment of greater structural homogeneity of the material and a reduction of time and energy expended during processing. This work aims to perform the characterization of electrical properties of niobium pentoxide (Nb2O5) pure or doped with molybdenum (Mo) and to do an analysis of the influence of this doping when its sintering process occurs in muffle furnace or microwave. The properties characterized were the permittivity and loss tangent. Will be studied the viability of doping and/or processing the material for use as absorbent materials of electromagnetic radiation. The variation of concentrations in doping will indicate how effective, as a doping agent, molybdenum will be in the ceramic matrix, converting energy of microwave into heat energy. The results showed that the increase of doping of the niobium pentoxide with molybdenum (with 1% doping limit) combined with the sintering oven microwave increased the material conductivity values, making it more efficient in its use as absorber electromagnetic radiation